MENTAL ACCOUNTING DAN FAKTOR DEMOGRAFI: FENOMENA PENGGUNAAN KARTU KREDIT PADA PEGAWAI BANK DANAMON CABANG AMBON - Micrets Agustina Silaya; Grace Persulessy (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
Financial management is the process of how to manage financial resources are structured and systematic way to meet the needs of human life. In financial management, one often thinks partially. So that led to the use of money is not logical. This occurs because the individual financial decision making is heavily influenced by factors that are less well known in the financial models, ie psychological factors and social, one of which is the mental aspect of accounting. Mental accounting focuses on how one should respond and evaluate a situation when there are two or more possible outcomes, particularly how to combine the possibilities of these results. In mental accounting, individuals determine utility rates are different in each account wealth thus affecting their consumption decisions. The results of chi-square analysis shows that there is a relationship between demographic factors sex with mental accounting. Sedengkan other demographic variables such as age and income is not linked to mental accounting.Keywords: mental accounting, demographics, use of credit cards